Classification of three corynebacterial strains isolated from a small paddock in North Rhine-Westphalia: proposal of Corynebacterium kalinowskii sp. nov., Corynebacterium comes sp. nov. and Corynebacterium occultum sp. nov. Issue 8 (3rd August 2021) - Schaffert, Lena; Ruwe, Matthias; Milse, Johanna; Hanuschka, Katharina; Ortseifen, Vera; Droste, Julian; Brandt, David; Schlüter, Laura; Kutter, Yvonne; Vinke, Svenja; Viehöfer, Prisca; Jacob, Lucas; et al.
Abstract : Three novel corynebacterial species were isolated from soil sampled at a paddock in Vilsendorf, North Rhine-Westphalia, Germany. The strains were coccoid or irregular rod-shaped, catalase-positive and pale white to yellow-orange in colour. By whole genome sequencing and comparison of the 16S rRNA genes as well as the whole genome structure, it was shown that all three strains represent novel species of the family Corynebacteriaceae, order Corynebacteriales, class Actinobacteria . This project describes the isolation, identification, sequencing, and phenotypic characterization of the three novel Corynebacterium species. We propose the names Corynebacterium kalinowskii sp. nov. (DSM 110639 T =LMG 31801 T ), Corynebacterium comes sp. nov. (DSM 110640 T =LMG 31802 T ), and Corynebacterium occultum sp. nov. (DSM 110642 T =LMG 31803 T ).